Learning Strategies in Education for Democratic Citizenship - Spajić-Vrkaš, Vedrana (2000)
The main aspects of learning democratic citizenship: - multidimensional and wholistic concept of citizenship : legal, political, social/economic, cultural, European, global ; - exploratory and innovative approaches: studies and research, sites, training courses - the link between concepts/competencies, grassroot initiatives and training approaches - coopeartion and partnerships at all levels - practical exploration through the sites of citizenship - address the issue of empowerment (capacity building, self- development" etc.).